2018
DOI: 10.1007/s13311-018-0666-8
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diets for Adult Neurological Disorders

Abstract: The current review highlights the evidence supporting the use of ketogenic diet therapies in the management of a growing number of neurological disorders in adults. An overview of the scientific literature supporting posited mechanisms of therapeutic efficacy is presented including effects on neurotransmission, oxidative stress, and neuro-inflammation. The clinical evidence supporting ketogenic diet use in the management of adult epilepsy, malignant glioma, Alzheimer's disease, migraine headache, motor neuron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 166 publications
(162 reference statements)
1
84
0
5
Order By: Relevance
“…66,67 Lastly, ketogenic diet is increasingly used as an effective treatment for refractory seizures in adults, 68 another treatment modality thought to alter metabolic substrate availability even though the basic underlying mechanism is not completely understood. 69,70 Perhaps most importantly, our findings in conjunction with emerging clinical trials of neuroimaging markers of structural integrity in post-cardiac arrest comatose patients 17,18 also support the broad use of structural imaging protocols (including MRIs) in such patients. Lack of neuroimaging evidence for overwhelming neuronal injury in persistently comatose patients should prompt a vigorous attempt to promote brain activation and aggressive treatment of ongoing seizures or other varying persistent functional abnormalities seen after cardiac arrest.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…66,67 Lastly, ketogenic diet is increasingly used as an effective treatment for refractory seizures in adults, 68 another treatment modality thought to alter metabolic substrate availability even though the basic underlying mechanism is not completely understood. 69,70 Perhaps most importantly, our findings in conjunction with emerging clinical trials of neuroimaging markers of structural integrity in post-cardiac arrest comatose patients 17,18 also support the broad use of structural imaging protocols (including MRIs) in such patients. Lack of neuroimaging evidence for overwhelming neuronal injury in persistently comatose patients should prompt a vigorous attempt to promote brain activation and aggressive treatment of ongoing seizures or other varying persistent functional abnormalities seen after cardiac arrest.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, recent studies have shown that super‐refractory status epilepticus, as seen in Patient 1, may remit with the use of ketamine, another NMDA‐antagonist agent . Lastly, ketogenic diet is increasingly used as an effective treatment for refractory seizures in adults, another treatment modality thought to alter metabolic substrate availability even though the basic underlying mechanism is not completely understood …”
Section: Discussionmentioning
confidence: 99%
“…Ketogenic diets (KDs) for the dietary management of epilepsy and neurometabolic conditions have undergone a worldwide renaissance and a reported increase in use over recent decades . Clinical and scientific research has confirmed degrees of efficacy , revealed possible mechanistic insights and, more recently, indicated their potential as adjunctive treatments for an ever‐widening range of other medical conditions . However, acceptability of KDs and adherence to the requisite, habitual, very low‐carbohydrate, very high‐fat intake is known to be variable and problematic, particularly for adults .…”
Section: Introductionmentioning
confidence: 99%
“…A high-fat, low-carbohydrate, ketogenic diet can alleviate symptoms including generalized pain and headache in a wide variety of neurological diseases, e.g., brain cancer, multiple sclerosis, neurotrauma, Alzheimer, and Parkinson disease [89]. Over the past decade, investigators have demonstrated the neuroprotective role of ketogenic diet [89][90][91].…”
Section: Enriched Polyunsaturated Fatty Acid Dietsmentioning
confidence: 99%